Chromatin in fractal globule state: evidence from comet assay - Afanasieva, K.S.; Chopei, M.I.; Sivolob, A.V. (Вiopolymers and Cell, 2015)
At higher order levels chromatin is organized into loops that appear as a result of contacts between distant loci. The aim of this work was to investigate the length distribution of the DNA loops in nucleoids obtained after lysis of either whole cells or isolated cell nuclei. Methods. We used single cell gel electrophoresis to analyze the kinetics of the DNA loop migration from the two nucleoid types. Results. The kinetics of the DNA exit was found to have specific features for the two types of nucleoids. At the same time, in both cases, the DNA amount in the electrophoretic track depends linearly on the length of the longest loops in the track. Conclusions. We have concluded that for the loops up to ~ 100 kb the length distribution appears to be consistent with the fractal globule organization.